2020
DOI: 10.1021/acs.jpcc.0c07735
|View full text |Cite
|
Sign up to set email alerts
|

Optical Force-Induced Dynamics of Assembling, Rearrangement, and Three-Dimensional Pistol-like Ejection of Microparticles at the Solution Surface

Abstract: Optical trapping and assembling dynamics of polystyrene (PS) microparticles (MPs) of 1 µm diameter is studied at its solution-air surface using a widefield microscope. Upon switching on the intense 1064 nm laser, the MPs are gathered, forming a single concentric circle (CC)-like assembly larger than the focus. It consists of a few tens of MPs and the central part of the assembly shows structural color, which indicates that the assembly is also growing in the axial direction. The MPs are dynamically fluctuating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…This observation indicates that enhanced particle–particle interaction results in the observed HCP morphology. [ 43 ] In our previous work, we concluded that the CC‐like arrangement is the kinetic state of the assembly while the HCP arrangement is the thermodynamically stable form with a large activation barrier between both states. The photoexcitation of the YG dye molecules provides an alternative pathway to overcome the large activation barrier.…”
Section: Resultsmentioning
confidence: 99%
“…This observation indicates that enhanced particle–particle interaction results in the observed HCP morphology. [ 43 ] In our previous work, we concluded that the CC‐like arrangement is the kinetic state of the assembly while the HCP arrangement is the thermodynamically stable form with a large activation barrier between both states. The photoexcitation of the YG dye molecules provides an alternative pathway to overcome the large activation barrier.…”
Section: Resultsmentioning
confidence: 99%
“…The NPs coming from the outside are trapped there, leading to the expansion of the assembly, which we call optically evolved assembling [52,56] . The assembling and rearrangement of NPs are driven by optical force, which is made possible by CW laser [77] . It will be fruitful to study these processes at solution surfaces by femtosecond laser.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Later, we expanded this concept by optical trapping of MPs and nanoparticles (NPs) at interfaces. [ 19,23–25 ] Similar to the molecular case, trapped MPs/NPs at the focus scatter and propagate the trapping laser, expanding the optical potential outside the focal volume. For example, a disk‐like assembly is prepared for polystyrene (PS) MPs at the solution surface, growing up to an area larger than 150 μm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a disk‐like assembly is prepared for polystyrene (PS) MPs at the solution surface, growing up to an area larger than 150 μm 2 . [ 24 ] At the early stages, the assembly presents a large dynamic motion with frequent “pistol‐like” MPs ejection. Instead, a periodical crystalline structure is prepared, when the PS NPs are trapped at the solution/glass interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation